(3cJGH GdaUd ddhUd GdeOQL aj Gdfbds - (3GdNWjH GdHZOGOj , CMeO Hf Ydj Hf KGHJ , CHh HcQ , J (B463 (3g` s ((3CMeO Hf eMeO Hf YeQ GdcQOi s)
(3ChdgG (B:s
(3GdMeO ddg Ydi ShGHZ fYeGFg bGd GdEeGe GdMGaX CHh HcQ CMeO Hf Ydi Hf KGHJ GdNWjH QVi Gddg Yfg gPG cJGH PcQJ agj CMGOjK jTcd TCfgG Ydi LeGYI ef CUMGH GdMOjK hGdCKQ s
(3BNQgG (B:s
(3bGd fgi QShd Gddg Udi Gddg Ydjg hSde Cf jHGd ai GdeGA GdQGcO BNQ GdLRA GdQGHY s
(3GdfSNI HgG MhGTs
(3HBNQg ebGHdI eDQNI SfI (B676(3g`s
(3bQf GdfSN (B:s
(3GdbQf GdSGHYs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B1 - (3U (B172 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B2 - (3U (B3s
Keywords: (3GdMOjK h GdeUWdMs